PENGARUH LINGKUNGAN BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS VI MATA PELAJARAN AKIDAH AKHLAK DI MI Ya BAKII KESUGIHAN 01 - Alfin Nur Aziz; Wida Nurul 'Azizah (Jurnal Tawadhu, 2023)
This study aims to determine the influence of the learning environment on learning achievement in creed subjects. The research method carried out is experimental research. The sample selection method in this study is saturated samples. The number of samples used amounted to 32 respondents. Data analysis techniques use validity and reliability tests, statistical tests with t tests. The results of this study showed that there was an increase in Akidah Akhlak learning achievement with an average score of 68 higher than the control class which obtained an average score of 62 and there was an influence of the learning environment on student achievement of moral creed lessons based on t test testing, on significance (2 tailed) showing 0.000. On the basis of t-test decision making, if the significance number (2 tailed) is below < 0.05, it can be concluded that there is an influence of the independent variable on the dependent variable.